Prototipe Tungku Krusibel Kompak Mini - Arianto Leman; Febrianto Amri Ristadi; Adiaksa Gilang; Bima Bima; Galang Dwi (Jurnal Dinamika Vokasional Teknik Mesin, 2019)
Crucible furnace for metal casting practice is needed by Vocational High School since their graduated students should possess competence in casting field. A prototype of a mini compact crucible furnace is built as an effort to fulfill the needed of an appropriate furnace. It is a sustained development of previous works. This furnace is developed using Research and development method. The prototype of a mini compact crucible furnace that has been succeeded developed has a dimension of (330x330x750) mm and 46 kg of total weight. The furnace can be made from the used drum with heat isolator combining of ceramic blanket D.96 and castable TNC-17. It is able to melt 3 kg of aluminum and achieve 660 0C in 50 minutes with LPG consumption of 1,76 kg. The outside temperature of the furnace is in the safety limit while it is operated. However, the prototype of a mini compact crucible furnace needs further development to improve its performance and heat efficiency.Tungku krusibel untuk praktik pengecoran logam dibutuhkan oleh Sekolah Menengah Kejuruan karena lulusannya harus memiliki komptensi dibidang pengecoran. Sebuah prototipe tungku krusibel mini dibuat sebagai upaya untuk memenuhi kebutuhan tungku yang sesuai. Ini merupakan pengembangan berkelanjutan dari tungku-tungku sebelumnya. Prototipe tungku krusibel kompak mini dikembangkan dengan metode Reserach and Development. Prototipe tungku krusibel kompak mini yang berhasil dibuat berdimensi (330x330x750) mm dengan bobot total 46 kg. Tungku dapat dibuat dari drum bekas dengan isolator panas kombinasi dari selimut keramik D.96 dan castable TNC-17. Prototipe tungku mampu melelehkan 3 kg aluminium dan mencapai suhu 660 0C dalam 50 menit dengan kebutuhan LPG 1,76 kg. Suhu dinding luar tungku masih dalam batas aman saat dioperasikan. Bagaimanapun, prototipe tungku krusibel kompak mini perlu dikembangkan lebih lanjut untuk memperbaiki kinerja dan efisiensi panasnya.